The Influence of P2 and PC3 Polygonal Shaft Machining Parameters on the Quality of Machining Results Using a Mazak CNC Type QTE 200-MY SG - Syahrul Rhamadhan; Irza Sukmana; Rizal Adi Saputra; Novrinaldi (INSTEP Network, 2025)
Shafts are vital components in mechanical systems that function to transmit motion to elements such as rotors and gears. Although keyed and splined joints are commonly used due to their ease of manufacturing, polygonal shafts of the P2 and PC3 types according to DIN standards offer advantages in transmission efficiency and torque resistance. This study focuses on the CAD modeling, CAM simulation, and CNC machining of P2- and PC3-type coupling shafts. The modeling was carried out using SolidWorks based on DIN standard dimensions, while the CAM simulation was conducted using Esprit TNG. The machining process employed a Mazak CNC QTE 200-MY SG machine with parameter variations based on material type (carbon steel and stainless steel). Evaluation was performed through surface roughness measurements using a surface roughness tester and dimensional inspection using a Coordinate Measuring Machine (CMM). The results show that the toolpath runs optimally, and the depth of cut (DoC) has a significant effect on surface quality. A smaller DoC produces a smoother surface but requires longer machining time, whereas a larger DoC speeds up the process but reduces surface quality. Dimensional deviations from the CAD design are suspected to be caused by suboptimal quantity and distribution of reference points during CMM measurement.